every equations the the kind ax^2+bx+c=0 deserve to be solved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one when ± is enhancement and one as soon as it is subtraction.

You are watching: Which are the solutions of the quadratic equation? x2 = 9x + 6


This equation is in conventional form: ax^2+bx+c=0. Instead of 1 for a, 9 because that b, and also -6 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
*

3x2+9x-6=0 Two options were found : x =(-3-√17)/2=-3.562 x =(-3+√17)/2= 0.562 action by action solution : step 1 :Equation in ~ the end of action 1 : (3x2 + 9x) - 6 = 0 step 2 : action 3 ...
displaystylex=leftlbrace-2,frac12 ight brace Explanation: displaystyle6x^2+9x-6=0displaystyle extsolution 1:displaystyle extfactor the equation : ...
-x2+9x-6=0 Two services were uncovered : x =(-9-√57)/-2= 8.275 x =(-9+√57)/-2= 0.725 step by action solution : action 1 : action 2 :Pulling out like terms : 2.1 traction out choose factors : ...
-3x2+9x-6=0 Two options were discovered : x = 2 x = 1 action by action solution : step 1 :Equation in ~ the finish of action 1 : ((0 - 3x2) + 9x) - 6 = 0 step 2 : action 3 :Pulling out like terms : ...
2x2+x-6=0 Two solutions were uncovered : x = -2 x = 3/2 = 1.500 action by step solution : step 1 :Equation at the finish of step 1 : (2x2 + x) - 6 = 0 action 2 :Trying to factor by splitting the ...
3x2+x-6=0 Two options were found : x =(-1-√73)/6=-1.591 x =(-1+√73)/6= 1.257 step by action solution : action 1 :Equation in ~ the end of action 1 : (3x2 + x) - 6 = 0 action 2 :Trying to factor ...
More Items
*
*

*
*
*

All equations the the form ax^2+bx+c=0 can be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula provides two solutions, one once ± is addition and one when it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Substitute 1 for a, 9 for b, and -6 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one can be resolved by perfect the square. In order to finish the square, the equation must an initial be in the form x^2+bx=c.
Divide 9, the coefficient the the x term, by 2 to obtain frac92. Then include the square that frac92 to both political parties of the equation. This step makes the left hand next of the equation a perfect square.
Factor x^2+9x+frac814. In general, when x^2+bx+c is a perfect square, that can constantly be factored as left(x+fracb2 ight)^2.

See more: How Much Is 60 Ml In Ounces, Cups, Etc, 60 Ml Of Water In Ounces


Quadratic equations such together this one have the right to be addressed by a new direct factoring technique that go not require guess work. To usage the straight factoring method, the equation need to be in the kind x^2+Bx+C=0.
Let r and s be the factors for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where amount of determinants (r+s)=−B and also the product of determinants rs = C
Two number r and s amount up come -9 exactly when the median of the 2 numbers is frac12*-9 = -frac92. Friend can likewise see that the midpoint that r and s coincides to the axis of the contrary of the parabola represented by the quadratic equation y=x^2+Bx+C. The values of r and s are equidistant from the facility by one unknown quantity u. Express r and s v respect to change u.
*
*

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు